Spatial and temporal patterns of roost use by tree-dwelling barbastelle bats Barbastella barbastellus ... - Russo, Danilo; Cistrone, Luca; Jones, Gareth (Zenodo, 2005)
(Uploaded by Plazi for the Bat Literature Project) We evaluated the spatial and temporal patterns of roost switching behaviour by a tree‐dwelling population of barbastelle bats Barbastella barbastellus in a beech forest of central Italy. Switching behaviour was common to both sexes and did not depend on group size. We observed both individual and group switching, the latter often involving the abandonment of a roost tree on a single night. We suggest that behaviours such as flight activity around roosts or cavity inspection by bats play a role in recruiting group mates and coordinating their occupation of another site. Bats almost never crossed mountain ridges to use roosts located beyond them, possibly because ridges are regarded as boundaries delimiting main roosting areas. The rate of switching was lowest during the middle of the lactation period, probably to minimise problems related to the transportation of non‐volant young by their mothers. Although the maintenance of social relationship among bats ...